补充说明 - 《食品安全质量检测学报》编辑部 (食品安全质量检测学报, 2015)
<正>本刊2015年第5期(2015,(5):1525-1529)黄艳等作者"闽南乌龙茶烘焙的研究进展"一文中做如下更改:基金项目:质检公益性行业科研专项(K4714004A)、福建农林大学安溪茶学院青年骨干培养基金(K1515047A)Fund:Supported by the Project of Quality Inspection Industry of Public Welfare(K4714004A)and the Youth Training Fund of Anxi College of Tea Science in Fujian Agriculture and Forestry University(K1515047A)